O arquivo e a informação arquivística: da literatura científica à prática pedagógica no Brasil - Calderon, Wilmara Rodrigues [UNESP] (2011)
The identity of a scientific discipline is linked to the ability to clearly distinguish its object of study, apply its own methods and develop a specialized language so that it is possible to establish relationships at different levels, with other disciplines. Among the many challenges that the Archival Science has been exposed, the act of structuring in terms of specialized language is mentioned by theorists as being of great significance. Assuming that the consolidation of some basic concepts helps to move toward the development of the area, this study aimed to investigate, through a comparison, the conception of professors and theorists in this area about terms such as archive and archival information. The selected professors were those responsible for teaching fundamental aspects taught in the first series of courses on Archival Science in Brazil. The approach uses theoretical-descriptive analysis for exposure of the positioning of theorists and professors, it discusses to what extent there is correlation between these two groups. It was observed that the theoretical referential that supports archival education in Brazil is characterized by the approach of national authors who disseminate their scientific output in journals. The professors’ conception on the concepts reveals, at times, the shallowness with which the issue has been handled. Regarding the term archive, it seemed to be a greater boldness on professors’ part to present a definition that is nearly always a reflection of what the national literature professes. However, in relation to archival information, it is noticed that it is still a term that causes some discomfort in the archival community in general